The Intersectoral Collaboration Document for Cancer Risk Factors Reduction: Method and Stakeholder Analysis - Ali-Asghar Kolahi; Kambiz Abachizadeh; Ali Gol-Mohammadi; Elham Izadi; Ahmad-Reza Farsar (Shahid Beheshti University of Medical Sciences, 2016)
Background and Objective: Cancers are one of the most important public health issues and the third leading cause of mortality after cardiovascular diseases and injuries in Iran. The most common cancers reported in the recent years have been included skin, stomach, breast, colon, bladder, leukemia, and esophagus respectively. Control of cancer as one of the three main health system priorities of Iran, needs a specific roadmap and clear task definition for involved organizations. This study provides stakeholder analysis include determining the roles of Ministry of Health and Medical Education as the custodian of the national health and the duties of other beneficiary organizations to reduce the risk of cancer for cooperation with a scientific approach and systematic methodology. Materials and Methods: This health system research project was performed by participation of Social Determinants of Health Research Center of Shahid Beheshti University of Medical Sciences, Office of the Non-Communicable Diseases of the Ministry of Health and Medical Education and other stakeholders in 2013. At first, the strategic committee was established and the stakeholders were identified and analyzed. Then the quantitative data were collected by searching in national database concern incidence, prevalence, and burden of all types of cancers. At the last with the qualitative approach, a systematic review of the studies, documents and reports was conducted as well as conversing for the national strategic plans of Iran and other countries and the experts' views regarding management of the cancer risk factors. In practice, role and responsibilities of each stakeholder were practically analyzed. Then the risk factors identified and the effective evidence-based interventions were determined for each cancer and finally the role of the Ministry of Health were set as the responsible or co-worker and also the role of the other organizations separately clarified in each case.